2017
DOI: 10.1177/1077546317707877
|View full text |Cite
|
Sign up to set email alerts
|

Downstream flat plate as the flow-induced vibration enhancer for energy harvesting

Abstract: The prospect of harvesting energy from flow-induced vibration using an elastic square cylinder with a detached flat plate is experimentally investigated. The feasibility of flow-induced vibration to supply an adequate base excitation for micro-scale electrical power generation is assessed through a series of wind tunnel tests. The current test model of a single square cylinder is verified through a comparable pattern of vibration amplitude response with previous experimental study and two-dimensional numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…In fact, Cui et al [27] also has shown the similar results, where in their study, cylinder of α=22.5° had lower VIV amplitude compared to the others. Next, a region free from VIV and galloping was found at reduced velocity in the range of 10 ≤ UR ≤ 15 for α=0°, which is in agreement with Maruai et al [26]. Therefore, it can be said that for a square cylinder, a tranquil zone was found between the phenomena of VIV and galloping.…”
Section: Effect Of the Angle Of Attacksupporting
confidence: 89%
See 2 more Smart Citations
“…In fact, Cui et al [27] also has shown the similar results, where in their study, cylinder of α=22.5° had lower VIV amplitude compared to the others. Next, a region free from VIV and galloping was found at reduced velocity in the range of 10 ≤ UR ≤ 15 for α=0°, which is in agreement with Maruai et al [26]. Therefore, it can be said that for a square cylinder, a tranquil zone was found between the phenomena of VIV and galloping.…”
Section: Effect Of the Angle Of Attacksupporting
confidence: 89%
“…In their study, they stated that for an isolated square cylinder, only two significant flow-induced vibration behaviours can be observed, namely, VIV that occurs at lower branch velocity and galloping that occurs at higher branch velocity. To verify the data of the present study, the existing amplitude ratio of an isolated square cylinder [26] was compared with the square cylinder response of the present study, as shown in Fig. 9.…”
Section: Verification Of the Experiments Datamentioning
confidence: 63%
See 1 more Smart Citation
“…Numerous experimental and numerical studies can be found where the detached flat plate is applied as a control instrument by varying its position or length (Aabid et al, 2019;Ali et al, 2012;Anderson et al, 1997;Apelt et al, 1973Apelt et al, , 1975Bruneau et al, 2014;Dehkordi et al, 2011;Ding et al, 2021;Doolan, 2009;Hassanzadeh Saraei et al, 2021;S. Ul Islam et al, 2015;Shams Ul Islam et al, 2014;Liu et al, 2016;Maruai et al, 2018;Mat Ali et al, 2011;Nidhul et al, 2015;Ozono, 1999;Park et al, 2013;Rashidi et al, 2016;Roshko, 1954;Sakamoto et al, 1997;Turki, 2008;Zhou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Such testing is regularly performed in the aerospace (Allen et al, 2011; Füllekrug and Sinapius 1998) and civil engineering (Ghosh and Basu 2004; Razeto et al, 1994) industries. In the past three decades, there has been renewed interest in finding the response of structures to base excitations in other domains of engineering, especially energy harvesting (Hou et al, 2020; Maruai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%